Effects of a nurse-led structured home visiting program on quality of life and adherence to treatment in hemodialysis patients - Pooresmaeil, Mina; Iranpour, Sohrab; Aghamohammadi, Masoumeh (Frontiers in Public Health, 2023)
Purpose: This study aimed to determine the effects of a nurse-led structured home visit program on quality of life and adherence to treatment in patients undergoing hemodialysis. Methods: The study was quasi-experimental research in which 62 hemodialysis patients referred to Bu Ali hospital in Ardabil participated in two groups: intervention (n= 31) and control (n= 31). The intervention included a structured and planned home visit program that was performed in five stages over 3 months. Data collection tools were a demographic information form, Kidney Disease Quality of Life Short Form (KDQOL–SF™) and End Stage Renal Disease Adherence Questionnaire (ESRD_AQ) which were completed by patients before, at the end of the first, second, and third month of intervention. SPSS v20 software and descriptive and analytical tests (Chi-square, t-test, ANOVA and repeated measure) were used for data analysis. Findings: Examining demographic characteristics showed that there is a negative and significant relationship between age and quality of life scores (P=0.004), that is, with increasing age, the quality of life score decreases, but other demographic characteristics did not have a significant relationship with quality of life scores and adherence to treatment (P>0. 05). Also, the results showed that in the intervention and control groups, during the study, the scores of quality of life and adherence to treatment increased significantly, and this increase was significantly higher in the intervention group than in the control group (P<0.001). The scores of quality of life and adherence to treatment increased significantly both during the study in each group separately and between groups during the study (P<0.001). Conclusions: According to the significant improvement in quality of life and adherence to treatment in patients following a home-visiting program during three months, these interventions can be utilized to improve quality of life and adherence to treatment of patients undergoing hemodialysis. Practice Implications: Home visiting programs significantly improve the level of knowledge of patients undergoing hemodialysis and their family members, through their involvement in the care process. Having said that, it seems plausible to implement home visits in the standard care plans of hemodialysis patients.